Investigation on the transient impact characteristics of fast switching valve during excitation stage - Gao, Qiang (Journal of low frequency noise, vibration, and active control, 2022)
Fast switching valve (FSV) inevitably experiences high-speed impact while obtaining high dynamics, which affects its control accuracy and service life. In this article, the impact characteristics of the FSV during the excitation stage are investigated. Firstly, a nonlinear mathematical model considering the magnetic saturation is established and verified. Then, the influences of three types of driving voltages on the initial impact velocity and the opening time of the FSV are analyzed, which proves that only the driving voltage featured by an interval of negative voltage (−24V) can obtain a good balance between the initial impact velocity and opening time. In addition, finite element simulations of transient impact characteristics show that smaller initial impact velocity is beneficial to reduce the impact displacement, equivalent stress, and wear volume. The influences of impact times on the flow area of the valve seat are quantitatively analyzed under different impact velocities. Theoretical results indicate that, compared to the high driving voltage, the variation of flow area per million impacts is reduced by 27.3% under the presented driving voltage. Finally, experimental results demonstrate that with the presented driving voltage, the average acceleration and the average noise are reduced by 65.7% and 12%, respectively. And the acceleration frequency spectrum and the modal simulation both reveal the composition of impact noise, in which the noise heard by the human ear is mainly impacted noise, not the ringing noise.